Fluctuations of intracellular forces during cell protrusion - Ji, Lin (2008)
We propose a model to infer from live cell images of actin filament (F-actin) flow intracellular force variations during protrusion-retraction cycles of epithelial cells in a wound healing response. To establish mechanistic relations between force development and cytoskeleton dynamics, force fluctuations were correlated with fluctuations in F-actin turnover, flow, and F-actin-vinculin coupling. Our analyses suggest that force transmission at focal adhesions (FA) requires binding of vinculin to F-actin and integrin (indirectly), which is modulated at the vinculin-integrin but not the vinculin-F-actin interface. Force transmission at FAs is co-localized in space and synchronized in time with transient increases of the boundary force at the cell edge. Surprisingly, the maxima in adhesion and boundary forces lag maximal edge advancement by ∼40 s. Maximal F-actin assembly is observed ∼20 s after maximal edge advancement. Based on these findings, we propose that protrusion events are limited by membrane tension and that the characteristic duration of a protrusion cycle is determined by the efficiency in reinforcing F-actin assembly and adhesion formation as tension increases.